Arm muscle power, eye-hand coordination, and psychological distress predict jab-straight punch frequency - Edy Dharma Putra Duhe; I Kadek Suardika; Suprianto Kadir; Meri Haryani; Safri Irawan (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2026)
Jab-straight punch frequency is an important indicator of repeated punching performance in boxing and may be associated with physical, coordinative, and psychological characteristics. This study examined associations between arm muscle power, eye-hand coordination, and GHQ-12 psychological distress scores and jab-straight punch frequency among boxing athletes registered under PERTINA Gorontalo Province. A quantitative cross-sectional correlational design with multiple linear regression analysis was used. All 15 eligible athletes were included through total sampling; therefore, the findings apply only to this study sample. Arm muscle power, eye-hand coordination, and psychological distress scores were assessed using the Seated Medicine Ball Throw, Wall Toss Test, and General Health Questionnaire-12, respectively. Jab-straight punch frequency was defined as the number of valid punches completed within 30 seconds. The regression model was statistically significant, F(3, 11) = 108.799, p < .001, R² = .967, and adjusted R² = .959. Eye-hand coordination showed a positive regression coefficient (B = 1.616, p < .001), whereas arm muscle power (B = −3.155, p = .043) and psychological distress scores (B = −0.216, p < .001) showed negative coefficients. Higher psychological distress scores were associated with lower jab-straight punch frequency. These findings may provide preliminary information for evaluating the measured variables within this sample. Future studies with larger, more diverse samples and specific biomechanical tools are needed to further examine these associations.